The mind's blue eye : Berkeleian casts in the poetry of Richard Wilbur - O'Keeffe, William John (Trinity College (Dublin, Ireland). School of English, 2001)
One is struck, throughout the poetry of Richard Wilbur, by a tantalizing resemblance to the work of two close contemporaries: Howard Nemerov in the United States and Philip Larkin in Great Britain. Wilbur admired both, rating Nemerov pre-eminent in the United States. And yet, Wilbur refuses to be the Larkin or the Nemerov of America. The guardedly celebratory conservatism of Larkin is there in Wilbur, as are the ingeniously constructed poetic forms; the moral wryness of Nemerov is there too, with the New Critical preference for the tight lyric. There is, in addition, an unpredictability in the poems, leading to sharp shifts, often turning on a multiple pun, and, above all, an observer's detachment that accords attention and significance to light, colour, and movement. These extra qualities are scarcely unique grounds for claiming distinction for Wilbur's poetry. Rather, over and above these, he seems to have an intuitive conviction of the mind-extending possibilities so empirically worked out in Berkeley's essays on the theory of vision and the principles of human knowledge. There is a paradox in a poet who happily takes licence from Berkeley, the philosopher who sought to strip the 'garniture' of words from pure ideas. Wilbur seeks to de-construct visual and sensory world as Berkeley does [cf. An Event, NCP 274; Epistemology, NCP 288], but then to re-clothe it in appropriate words. It is this very emphasis on words, always on the exact, nicely judged word, that is the main delight of the poetry and the necessarily central focus of this thesis. The poetry is examined for its thematic threads of order-in-disorder, synaesthesia of sound and sight, and for the yield of Wilbur's own area of empirical experiment: the hypnopompic and hypnagogic states. ...
Keywords: English, M.Litt.; M.Litt. Trinity College Dublin